Exploration of Islamic Values in Islamic Banking (Study of Islamic Bank Customer Perspective in Makassar) - Misbach, Irwan (Jurnal Minds: Manajemen Ide dan Inspirasi, 2019)
This study explores Islamic values in the operations of Islamic banks based on the perspective of customers in Makassar City. Based on factor analysis, 4 factors are found. Factor 1 contains "Islamic Products" which are “Amanah”. Factor 2 contains "Islamic Performance" which is Tabliqh. Factor 3 contains "reliability or Islamic Assurance" that is identical to Sidiq. Factor 4 contains "Islamic services" that are identical to Fathanah. This research is able to form Islamic Corporate Governance indicators that respond to research challenges about the initial concept of Islamic-corporate-governance implementation in Islamic banks through mandate in their products, tabliq in providing guarantees to customers, shiddiq which is reliability like syariah, and fathanah in serving customers in banking transaction.